Second Language Learners’ Competence of and Beliefs About Pragmatic Comprehension: Insights From the Chinese EFL Context - Yang, He (Frontiers in Psychology, 2022)
It can be a great challenge for second language (L2) learners to comprehend meanings that are implied in utterances rather than the surface meaning of what was said. Moreover, L2 learners’ attitudes toward pragmatic learning are unknown. This mixed-methods study investigates L2 learners’ ability to comprehend conversational implicatures. It also explores their beliefs about and intentions to develop this ability using Ajzen’s theory of planned behavior (TPB). A total of 498 freshmen from a public university in China participated in the study. Data were collected using a web-based test, stimulated recall tasks and semi-structured interviews. Results show that the participants differed in recognizing the intended meanings. Complicated factors account for the variations. In addition to the types of implicature, learners’ beliefs about developing pragmatic comprehension also influence their learning intention, and subsequent performance. These beliefs include learners’ multi-layered, complex attitudes toward the outcomes of pragmatic learning, perceived self-efficacy beliefs regarding language proficiency and L2 cultural knowledge, actual behavioral control over opportunities and resources for pragmatic learning, and perceptions of less social pressure on pragmatic learning. The use of TPB may help language teachers and test designers to understand learners’ beliefs about L2 pragmatic learning in the English as a foreign language (EFL) context. Understanding the factors influencing learners’ intention will help design more effective teaching curricula that may integrate pragmatic instruction and testing in the future.